2020
DOI: 10.3390/v12101198
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to Canine Adenovirus-2 Virus Vaccination in Healthy Adult Dogs

Abstract: Background: Re-vaccination against canine adenovirus (CAV) is performed in ≤3-year-intervals but their necessity is unknown. The study determined anti-CAV antibodies within 28 days of re-vaccination and factors associated with the absence of antibodies and vaccination response. Methods: Ninety-seven healthy adult dogs (last vaccination ≥12 months) were re-vaccinated with a modified live CAV-2 vaccine. Anti-CAV antibodies were measured before vaccination (day 0), and after re-vaccination (day 7, 28) by virus ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Based on the previous studies, a relationship has been observed between the absorbed MDA and the duration of protection, which is proof of the importance of colostrum in newborn puppies [ 24 ]. Despite this, MDA has decreased over time and most studies have reported that the MDA protective titer exists until 13–15 weeks of age [ 27 ]. In this regard, some solutions can be used to nullify the MDA interference such as determining the MDA titer, alternative of injective vaccines in the young puppies, use high-titer vaccines in areas with high prevalence [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous studies, a relationship has been observed between the absorbed MDA and the duration of protection, which is proof of the importance of colostrum in newborn puppies [ 24 ]. Despite this, MDA has decreased over time and most studies have reported that the MDA protective titer exists until 13–15 weeks of age [ 27 ]. In this regard, some solutions can be used to nullify the MDA interference such as determining the MDA titer, alternative of injective vaccines in the young puppies, use high-titer vaccines in areas with high prevalence [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In field studies, antibodies were present after 6 to 14 years [ 17 , 18 ]. Individual dogs, however, were more likely to lack antibodies if the last vaccination was given >3 [ 19 ] and ≥4 years [ 20 ] ago. Currently, guidelines recommend 3-yearly boosters for vaccination against ICH [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, antibody testing can be useful to evaluate the dog’s vaccination response; the absence of anti-CAV antibodies in dogs after vaccination indicates a non-response, (e.g., due to interference with maternally derived antibodies, pre-existing antibodies due to previous infection or vaccination, or immunodeficiency [ 19 ]). Further, antibody testing is helpful for the separation of dogs during the management of disease outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…CAV-2 provokes disorders in the respiratory organs, including tonsillitis, pharyngitis, tracheitis, bronchitis, and having an affinity for the epithelium of the upper respiratory tract. This virus was first detected in Canadian shelter dogs in 1961 with symptoms of upper respiratory tract infection, and in the following years its presence was reported in many countries such as Italy, Brazil, and India (Hechinger et al, 2017;Ramidi et al, 2019;Bergmann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%